2001
DOI: 10.1093/carcin/22.1.73
|View full text |Cite
|
Sign up to set email alerts
|

Oral administration of naturally occurring coumarins leads to altered phase I and II enzyme activities and reduced DNA adduct formation by polycyclic aromatic hydrocarbons in various tissues of SENCAR mice

Abstract: Several naturally occurring coumarins, to which humans are routinely exposed in the diet, were previously found to inhibit P450-mediated metabolism of benzo[a]pyrene (B[a]P) and 7,12-dimethylbenz[a]anthracene (DMBA) in vitro, block DNA adduct formation in mouse epidermis and inhibit skin tumor initiation by B[a]P and/or DMBA when applied topically to mice. The present study was designed to investigate the effects of two of these compounds, of the linear furanocoumarin type, when given orally (70 mg/kg per os, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
46
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(48 citation statements)
references
References 38 publications
2
46
0
Order By: Relevance
“…Kleiner et al [2001] demonstrated that the CYP inducing effects of furanocoumarins, imperatorin and isopimpinellin were apparently found in the liver, because the CYP activities in skin epidermis, forestomach, and lung remained unchanged or suppressed at 24 hr after the last of 4 consecutive oral doses in mice. In addition, the DNA adduct formation by B[a61533P and/or DMBA was also reduced by NOFs in these tissues [Kleiner et al, 2001]. Perhaps the hepatic CYPs, GSTs, and NAD(P)H quinone oxidoreductase coupled with sustained suppression of CYPs in the extrahepatic tissues allowed these carcinogens to be metabolized and cleared in the liver.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kleiner et al [2001] demonstrated that the CYP inducing effects of furanocoumarins, imperatorin and isopimpinellin were apparently found in the liver, because the CYP activities in skin epidermis, forestomach, and lung remained unchanged or suppressed at 24 hr after the last of 4 consecutive oral doses in mice. In addition, the DNA adduct formation by B[a61533P and/or DMBA was also reduced by NOFs in these tissues [Kleiner et al, 2001]. Perhaps the hepatic CYPs, GSTs, and NAD(P)H quinone oxidoreductase coupled with sustained suppression of CYPs in the extrahepatic tissues allowed these carcinogens to be metabolized and cleared in the liver.…”
Section: Discussionmentioning
confidence: 99%
“…For example, another chemopreventive agent oltipraz is thought to suppress hepatocarcinogenesis due to aflatoxin B 1 through the induction of glutathione S-transferases (GSTs), but it is also found to modulate hepatic CYP by acting both as a reversible inhibitor and an inducer of CYP1A and CYP2B [Langouet et al, 1997]. Kleiner et al [2001] demonstrated that the CYP inducing effects of furanocoumarins, imperatorin and isopimpinellin were apparently found in the liver, because the CYP activities in skin epidermis, forestomach, and lung remained unchanged or suppressed at 24 hr after the last of 4 consecutive oral doses in mice. In addition, the DNA adduct formation by B[a61533P and/or DMBA was also reduced by NOFs in these tissues [Kleiner et al, 2001].…”
Section: Discussionmentioning
confidence: 99%
“…However, when cisplatin was used as a second-line therapy with doses varying from 60 to 175 mg/m 2 /cycle, the RR ranged from 0 to 40% (table 1) [6,7,8,9,10,11]. …”
Section: Experience With Single-agent Therapymentioning
confidence: 99%
“…4-CPA treatment of the mice had no significant effect on either basal or DMBA-induced EROD activity. Measurement of EROD activity in the presence of mammary microsomal protein was more difficult due to the lower yield of microsomes and CYP1 levels [23]. Therefore, we pooled mammary derived microsomes obtained from 5 mice in each treatment group in order to obtain enough protein for detecting EROD activity.…”
Section: -Cpa Does Not Interfere With Activity Of P450 Enzymes Cyp19mentioning
confidence: 99%